2019
DOI: 10.1007/s40801-019-0157-1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of High-Dose and Long-Term Proton Pump Inhibitor Use: A Cross-Sectional Study in Six South Australian Residential Aged Care Services

Abstract: Aim While proton pump inhibitors (PPIs) are generally considered safe and well tolerated, frail older people who take PPIs long term may be susceptible to adverse events. This study characterized PPI use and determined factors associated with high-dose use among older adults in residential aged care services (RACSs). Methods A cross-sectional study of 383 residents of six South Australian RACSs within the same organization was conducted. Clinical, diagnostic, and medication data were collected by study nurses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Given that GPs in our study reported discussing these topics, the PPI deprescribing practices of these GPs appeared to generally align with patient views surrounding PPI deprescribing discussions. Patients in our study were generally open to discussing deprescribing, which is consistent with a recent Australian study of PPI users [16].…”
Section: Comparison With Existing Literaturesupporting
confidence: 89%
“…Given that GPs in our study reported discussing these topics, the PPI deprescribing practices of these GPs appeared to generally align with patient views surrounding PPI deprescribing discussions. Patients in our study were generally open to discussing deprescribing, which is consistent with a recent Australian study of PPI users [16].…”
Section: Comparison With Existing Literaturesupporting
confidence: 89%
“…Study designs included observational studies (n=31), experimental studies (n=6), qualitative studies (n=2), and a methodological study (n=1) (Table 1 ). Six articles utilized data from an Australian cohort study ( 23 , 25 , 26 , 29 31 ), five from an Australian randomized controlled trial (RCT) ( 22 , 27 , 28 , 32 , 33 ), three from a Spanish longitudinal study ( 41 43 ), and three from a Chinese cross-sectional study ( 35 37 ). The number of participants ranged from 13 to 571,139, with a mean age range of 79.0 ± 8.8 to 89.4 ± 4.6 years.…”
Section: Resultsmentioning
confidence: 99%
“… 35 In our study, we found that high-dose therapy was most frequently prescribed (73%) compared with standard (23%) and low-dose therapy (3.6 %), which was similar to the findings of the result in Australia in 2017 16 but higher than other studies. 12 The effect of dose and type of PPI research has shown that high doses of PPIs could increase the risk of chronic kidney disease at an impressive level (92%) for any kind of PPI exposure, and this risk increased even more when doing the follow-up. 36 There are pieces of evidence to suggest that high-dose PPIs can lead to the development of hypomagnesemia, 37 and increase the risk of osteoporotic fractures 38 and serious cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, once symptoms were adequately relieved, a ‘step down’ therapy is recommended to reduce the dose to the lowest effective dose through a periodic reassessment of patients. 12 42 Together, these collective shreds of evidence highlight the importance of doctors in collaborative practices with supervisor pharmacists to develop innovative practices to provide economic, effective and safe pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation